Disputed Boundaries of the Self, the Group, and their Environment: What We Learn from Refugees about our Psychic Functioning 1 - Luci, Monica (Journal of analytical psychology, 2024)
One of Jung’s most significant contributions concerns the mysterious, inexplicable and always out‐of‐reach nature of the self. In this paper, I will focus on the borders of the self and their nature, location and dynamics of maintenance and change in geographically, historically, and culturally situated subjects. Reflecting on the refugee experience, I intend to gain more insights into our psychic functioning and the dynamics of the self in relation to itself, the other and groups. The experiences of some refugees, marked bysignificant trauma and migration, shed light on how the boundaries of the self are frequently contested and perpetually negotiated with others, and how our subjectivity is shaped by ongoing dynamics of occupation, dispute and/or negotiation, conducted at various levels of our social and individual existence. My argument is that these processes occur at a specific site: the boundaries of the self, involving intrapsychic, interpersonal and group psychological dynamics, with reverberations in the socio‐political and cultural spheres, and reciprocal influences between all these levels. This paper aims to concentrate on the shifts in these boundaries, illustrated through clinical vignettes. L'une des contributions les plus précieuses de Jung concerne la nature du soi. Celle‐ci est mystérieuse, inexplicable et toujours inaccessible. Dans cet article, réfléchissant à l'expérience de certains réfugiés et essayant d'en extraire plus de connaissances sur notre fonctionnement psychique et la dynamique du soi en relation avec le soi, l’autre et les groupes, je me concentrerai sur les frontières du soi et leur nature, leur localisation, et sur la dynamique de leur maintien et de leur changement chez des sujets géographiquement, historiquement et culturellement situés. L'expérience de certains réfugiés, qui combine un traumatisme majeur et l'expérience de la migration, est particulièrement éclairante sur la façon dont les limites de soi sont souvent contestées et toujours négociées avec les autres, et sur la façon dont notre subjectivité est le résultat de dynamiques continues d'occupation, de conflit et/ou de négociation, menées à différents niveaux de nos vies sociales et individuelles. Mon argument est que ces processus se produisent aux frontières du soi, impliquant des dynamiques psychologiques intrapsychiques, interpersonnelles et de groupe, avec des répercussions dans les sphères sociopolitiques et culturelles, avec des influences réciproques entre tous ces niveaux. L'objectif est de se concentrer sur les changements dans ces limites, en les illustrant par des vignettes cliniques. Einer von Jungs wertvollsten Beiträgen betrifft die mysteriöse, unerklärliche und stets unerreichbare Natur des Selbst. In diesem Artikel werde ich mich auf die Grenzen des Selbst und seine Natur, Lage und Dynamik der Erhaltung und Veränderung in geographisch, historisch und kulturell verorteten Themen konzentrieren. Dabei werde ich über die Erfahrungen einiger Flüchtlinge nachdenken und versuchen, daraus mehr Wissen über unsere psychische Funktionsweise und die Dynamik des Selbst in Bezug auf uns selbst, auf andere und auf Gruppen zu gewinnen. Die Erfahrungen einiger Flüchtlinge, die schwere Traumata und die Erfahrung der Migration kombinieren, verdeutlichen besonders, wie die Grenzen des Selbst oft umstritten sind, immer mit anderen ausgehandelt werden und wie unsere Subjektivität das Ergebnis andauernder Dynamiken der Besetzung, Auseinandersetzung und/oder Verhandlung ist, die auf verschiedenen Ebenen unseres gesellschaftlichen und individuellen Lebens stattfinden. Ich behaupte, daß diese Prozesse an den Grenzen des Selbst stattfinden und intrapsychische, zwischenmenschliche und gruppenpsychologische Dynamiken mit Auswirkungen auf die soziopolitische und kulturelle Sphäre mit gegenseitigen Einflüssen zwischen all diesen Ebenen umfassen. Der Versuch besteht darin, sich auf die Veränderungen an diesen Grenzen zu konzentrieren und sie mit klinischen Vignetten zu illustrieren. Uno dei contributi più importanti di Jung riguarda la misteriosa, inspiegabile e sempre irraggiungibile natura del Sé. In questo articolo, mi concentrerò sui confini del Sé e sulla loro natura, collocazione e dinamiche di mantenimento e cambiamento in soggetti situati geograficamente, storicamente, e culturalmente, riflettendo sull’esperienza di alcuni rifugiati e cercando di estrarre da ció maggiori conoscenze sul nostro funzionamento psichico e sulle dinamiche del Sé in relazione a se stessi, agli altri ed ai gruppi. L’esperienza di alcuni rifugiati, che combina un trauma importante con l’esperienza della migrazione, è particolarmente illuminante su come i confini del Sé siano spesso contestati e sempre negoziati con gli altri, e su come la nostra soggettività sia il risultato di dinamiche continue di occupazione, disputa e/o negoziazione, condotte a diversi livelli della nostra vita sociale e individuale. La mia tesi è che questi processi avvengono ai confini del Sé, coinvolgendo dinamiche psicologiche intrapsichiche, interpersonali e di gruppo, con riverberi nelle sfere socio‐politiche e culturali, e con influenze reciproche tra tutti questi livelli. Il tentativo è concentrarsi sui cambiamenti in questi confini, illustrandoli con vignette cliniche. Наиболее ценный вклад Юнга касается таинственной, необъяснимой и непостижимой природы самости. Предметом данной статьи являются границы самости, а также их природа, местонахождение и динамика их удержания и изменения у субъектов в определенных географических, исторических и культурных условиях. Я размышляю об опыте ряда беженцев и пытаюсь таким образом побольше узнать о нашем психическом функционировании и динамике самости в отношении самости, другого и группы. Опыт некоторых беженцев, сочетающий тяжелую психологическую травму с опытом миграции, особенно наглядно демонстрирует, что границы самости часто атакуются и нуждаются в согласовании с другими, а наша субъектность является следствием постоянной динамики вторжений, споров и/или переговоров, происходящих на разных уровнях нашей общественной и индивидуальной жизни. Я полагаю, что эти процессы протекают на границах самости, задействуя внутрипсихическую, межличностную и групповую психологическую динамику и отражаясь на социально‐политической и культурной сферах, при том, что все эти уровни оказывают взаимное влияние друг на друга. В фокусе моего внимания находится изменение этих границ, что иллюстрируется клиническими примерами. Una de las contribuciones más valiosas de Jung se refiere a la naturaleza misteriosa, inexplicable e inalcanzable del self. En este artículo, me centraré en las fronteras del self y su naturaleza, localización y dinámicas de mantenimiento y cambio en sujetos geográfica, histórica y culturalmente situados, reflexionando sobre la experiencia de algunos refugiados e intentando extraer de ella más conocimiento sobre nuestro funcionamiento psíquico y la dinámica del self con relación a sí mismo, el otro y los grupos. La experiencia de algunos refugiados, que combina traumas de gravedad y la experiencia de la migración, es particularmente esclarecedora de cómo los límites del self, a menudo son disputados y siempre negociados con otros, y de cómo nuestra subjetividad es el resultado de dinámicas continuas de ocupación, disputa y/o negociación, llevadas a cabo en diferentes niveles de nuestras vidas sociales e individuales. Mi argumento es que estos procesos ocurren en las fronteras del self, involucrando dinámicas psicológicas grupales, intrapsíquicas e interpersonales, con repercusiones en las esferas sociopolítica y cultural, con influencias recíprocas entre todos estos niveles. La intención es hacer foco en los cambios en estas fronteras, ilustrándolos con viñetas clínicas. 自我、群体及其环境的争议性边界:我们从难民身上学到了什么? 荣格最有价值的贡献之一是关于自性的神秘性、不可解释性和永远无法触及性。在本文中, 我将重点关注自性的边界及其性质, 其位置和维系的动力, 以及其在不同地理、历史和文化背景下生活的个体身上的差异, 本文将反思一些难民的经历, 并试图从中提取更多认识, 以理解我们的心理功能, 以及自性与自我、他人和群体之间的动态关系。 有一些难民的经历中包括了重大创伤和迁徙的经历, 这些特别能说明自性的边界如何经常受到争议, 如何总是需要与他人进行谈判, 以及我们的主体性如何来自于一个持续不断的占领、争议和/或谈判的过程, 这些过程发生在社会和个人生活的不同层面。 我的论点是, 这些过程发生在自性的边界上, 涉及心理内部、人际关系和群体心理动态, 并在社会政治和文化领域产生反响, 所有这些层面之间存在相互影响。我试图将重点放在这些界限的变化上, 并通过临床案例加以说明。